A Graphene-Based Bioactive Product with a Non-Immunological Impact on Mononuclear Cell Populations from Healthy Volunteers - María del Prado Lavín-López; Mónica Torres-Torresano; Eva María García-Cuesta; Blanca Soler-Palacios; Mercedes Griera; Martín Martínez-Rovira; José Antonio Martínez-Rovira; Diego Rodríguez-Puyol; Sergio de Frutos (Nanomaterials)
We previously described GMC, a graphene-based nanomaterial obtained from carbon nanofibers (CNFs), to be biologically compatible and functional for therapeutic purposes. GMC can reduce triglycerides’ content in vitro and in vivo and has other potential bio-functional effects on systemic cells and the potential utility to be used in living systems. Here, immunoreactivity was evaluated by adding GMC in suspension at the biologically functional concentrations, ranging from 10 to 60 µg/mL, for one or several days, to cultured lymphocytes (T, B, NK), either in basal or under stimulating conditions, and monocytes that were derived under culture conditions to pro-inflammatory (GM-MØ) or anti-inflammatory (M-MØ) macrophages. All stirpes were obtained from human peripheral mononuclear cells (PBMCs) from anonymized healthy donors. The viability (necrosis, apoptosis) and immunological activity of each progeny was analyzed using either flow cytometry and/or other analytical determinations. A concentration of 10 to 60 µg/mL GMC did not affect lymphocytes’ viability, either in basal or active conditions, during one or more days of treatment. The viability and expression of the inflammatory interleukin IL-1β in the monocyte cell line THP-1 were not affected. Treatments with 10 or 20 µg/mL GMC on GM-MØ or M-MØ during or after their differentiation process promoted phagocytosis, but their viability and the release of the inflammatory marker activin A by GM-MØ were not affected. A concentration of 60 µg/mL GMC slightly increased macrophages’ death and activity in some culture conditions. The present work demonstrates that GMC is safe or has minimal immunological activity when used in suspension at low concentrations for pre-clinical or clinical settings. Its biocompatibility will depend on the dose, formulation or way of administration and opens up the possibility to consider GMC or other CNF-based biomaterials for innovative therapeutic strategies.